Peran Guru Dalam Penanaman Nilai Karakter Peduli Lingkungan Pada Anak 5-6 Tahun di RA Annajmush Shagir - Potabuga, Anita; Pratiwi, Wiwik; Indriani, Indriani (Prodi PIAUD STAI AL-GAZALI BONE, 2025)
The aim of this research is to find out more about the role of teachers in instilling environmentally caring character values ​​in children at RA Annajmus Shagir, Gorontalo City. This research uses qualitative research. Next, the researcher describes the research objects related to objects in early childhood in Raudhatul Athfal (RA) Annajmush Shagir, Gorontalo City. The data collection procedures in this research are observation, interviews and documentation. Activities in data analysis, namely data collection, data reduction, data presentation, and drawing conclusions and verification. Research Results The habit of maintaining cleanliness is carried out through character formation methods, especially the habituation method, which is effective in getting children used to maintaining cleanliness. Children are also taught to become a generation that is more responsible for environmental sustainability. Providing motivation in the form of small awards is also one way to encourage children to care more about cleanliness and waste sorting. Involve children in hygiene activities, and provide gentle monitoring and correction. However, even though various efforts have been made, it does not rule out the possibility of obstacles faced in cultivating the character value of caring for the environment, such as children who are less enthusiastic and very stupid in caring about the environment and a lack of adequate facilities.